Near Net Shape Fabrication of Ceramic Composite Tube by Thermal Spray Forming. (December 2018) - Mohammed, M A; Zaidan, Sh A; Smich, H A
Abstract: In the present study, a comparison has made between a prepared pure alumina tube and ceramic composite tubes fabricated by spray forming method with wall thickness of 1-2 mm and the diameter of 8-10 mm. Alumina with 5, 10, 15 and 20% of SiO2, Zirconia silicate with 5, 10, 15 and 20% of Al2 O3 and Zirconia silicate with 5, 10, 15 and 20% of TiO2 have been fabricated. A detailed characterization of the spray-formed Al2 O3 structure has performed using XRD, SEM, AFM and microhardness measurements. This study proved that a variety of structured materials and their combinations can be fabricated to near net shapes.